Faculty motivations to integrate international perspectives in public relations education - Bower, Myranda (Kansas State University, 2019)
A survey of public relations educators at accredited institutions in the United States revealed that faculty members are more intrinsically motivated to incorporate international perspectives in the curriculum than extrinsically motivated. The analysis also found that there is a relationship between cultural intelligence and incorporating multiculturalism and international public relations into curricula. The study contributes to the literature on self-determination theory and cultural intelligence and has practical implications for both educators and the future generation of PR practitioners.
Keywords: International Public Relations; Education; Motivations